2021
DOI: 10.1093/bjsw/bcab004
|View full text |Cite
|
Sign up to set email alerts
|

Casting Light on the Distinctive Contribution of Social Work in Multidisciplinary Teams for Older People

Abstract: The current policy emphasis in adult social care in England is on promoting independence, preventing or delaying the need for more intensive support and the provision of personalised services. However, there is little evidence available on how social workers (SWs) identify and meet the complex needs of older service users in practice. In this article, we present findings from a study of innovative social work practice with older adults in England (2018–2019). We present five case studies of social care and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The ability of practitioners to build trust and develop rapport was identified as crucial, as well as flexibility, empathy and attentiveness to the person, in context. These skills have been highlighted in other studies of assessment practice in nursing and social work with older people (Carradice, Shankland & Beail, 2002;Ray et al, 2015;Tanner, 2021;Willis et al, 2022). Certain formats and approaches were viewed as encouraging an unhelpful routinisation of the assessment process in a way that inhibited the development of trust and open conversation; whereas other formats, which allowed or promoted greater flexibility, whilst still offering a structure to the conversation, were perceived more favourably.…”
Section: Discussionmentioning
confidence: 92%
“…The ability of practitioners to build trust and develop rapport was identified as crucial, as well as flexibility, empathy and attentiveness to the person, in context. These skills have been highlighted in other studies of assessment practice in nursing and social work with older people (Carradice, Shankland & Beail, 2002;Ray et al, 2015;Tanner, 2021;Willis et al, 2022). Certain formats and approaches were viewed as encouraging an unhelpful routinisation of the assessment process in a way that inhibited the development of trust and open conversation; whereas other formats, which allowed or promoted greater flexibility, whilst still offering a structure to the conversation, were perceived more favourably.…”
Section: Discussionmentioning
confidence: 92%
“…Integration can take place in various ways (Robertson, 2011) but must focus on the service user's perspective (Bailey and Mutale, 2022;Boland et al, 2021;Henderson et al, 2021;Klinga et al, 2020;Perunovic, 2018;Van Raak, 2003;Willis et al, 2022). A continuum exists from co-operation between entirely separate organisations through the co-ordination of services in multidisciplinary networks (e.g.…”
Section: Integrated Well-being Service Developmentmentioning
confidence: 99%
“…Research has reported that social workers bring important social, cultural, and community perspectives to medical interdisciplinary teams (Giles, 2016). However, hospital social workers have expressed feeling institutional pressure from medical and healthcare professionals to discharging patients as soon as they are medically stable, which in turn social workers argue can hinder patient well-being and overall social work care planning (Willis et al, 2022). Given the high demand for physical and mental healthcare of patients in modern hospitals and medical settings, social workers are often forced to see patients only once during their visit.…”
Section: Social Work In Healthcarementioning
confidence: 99%